A PRACTICAL GUIDE TO THE IDENTIFICATION OF FRESHWATER SNAILS OF IRAN - A.Mansoorian (Tehran University of Medical Sciences, 1986)
This guide to the identification of Iranian freshwater snails has been prepared with aim of helping individuals involved in field work, but who have had no specialized training in taxonomy to differentiate snail specimens which they collect to certain groups by means of simple identification key. The guide pays special attention to the principal snail groups which transmit human Schistosomiasis such as Bulinus; as well as to Lymnaea, transmits Facioliasis. Thus, in most cases, with the aid of this key it should be bossible to discriminate whether or not certain specimens are potential snail host of human schistosome parasites or are merely snails of no particular medical of veterinary importance. Such knowledge is, of course, necessary before under taking any rational snail control measures.